Dolabrane-type diterpenoid and lignan constituents from the stem barks of Ceriops decandra (Griff.) W. Theob. - Linh, Kieu Thi Phuong; Chien, Nguyen Van; Trung, Nguyen Quoc; Thong, Vu Huy; Tuyen, Nguyen Van; Thao, Nguyen Phuong (Vietnam Journal of Science and Technology, 2020)
Three dolabrane-type diterpenoids (1‒3) and a lignan derivative (4) were isolated from a methanolic extract of C. decandra stem barks using various chromatographic separations. Their structures were elucidated to be tagalsine X (1), tagalsin P (2), ent-5α,2-oxodolabr-3-ene-3,15,16-triol (3), and (+)-pinoresinol (4) by detailed analysis via spectroscopic techniques (1D, 2D NMR, and ESI-MS data) as well as comparison with those reported. This is the first report of compound 4 from the Ceriops genus.